The Influence of Audio Lingual Method Toward Speaking Skill of the Eighth Grade Students at SMP Negeri 6 Bontoramba - Isnadila; Muliaty Ibrahim; Hasnani (CV. Eureka Murakabi Abadi, 2022)
This study aims to determine the effect of the audio lingual method on the speaking skills of class VIII students at SMP Negeri 6 Bontoramba. This research is an experimental study where there are two classes, namely the experimental class and the control class. The sample of this study was class VIII students consisting of 18 students for the experimental class and 18 students for the control class. The instrument in this study used tests, namely pre-test and post-test. The data in this study were obtained from tests that have been carried out, namely pre-test and post-test. The data were analysed using the SPSS version 22 application. The result of the study showed that the average pre-test score of students in the experimental class was 45.22 while the average post-test score of experimental 64.44, while the average pre-test of control class was 41.83 and the average post-test in the control class was 54.72 where Ha is accepted and Ho is rejected. Therefore, the reseacher concluded that there was an improvement in students’ speaking using the audio lingual method in the experimental class SMP Negeri 6 Bontoramba.